Development of the insurance sector and economic growth: an empirical analysis for 47 countries - Sabater Castro, Anelena (2017)
This paper studies the effect of the development of the life and nonlife insurance market on economic growth, as well as the conditions (degree of financial development, income and institutional environment) that affect the relationship between both variables. The Generalized Method of Moments (GMM) was used, with a dynamic panel data model for 47 countries between 1990 and 2014.  Results indicate that there is a positive impact of the development of the insurance market on economic growth. In addition, the relationship between the insurance market and economic growth decreases in a relatively sounder institutional environment. On the other hand, the positive impact of the development of the insurance market on economic growth is mitigated in high-income countries.